A three-dimensional multi-phase numerical model of DMFC utilizing Eulerian-Eulerian model. (5th March 2018) - Sun, Jing; Zhang, Guobin; Guo, Ting; Jiao, Kui; Huang, Xuri
Highlights: A 3D multiphase model of DMFC is developed based on the Eulerian-Eulerian model. The carbon dioxide in anode channel mainly accumulates at the AFC/ADL interface. The carbon dioxide produced in ACL is likely to accumulate under the inlet region. The higher the DMFC operating temperature, the more methanol crossover. The higher the temperature, the less carbon dioxide in DMFC due to the dissolution. Abstract: A three-dimensional multiphase model of DMFC (direct methanol fuel cell) is developed, in which the Eulerian-Eulerian model is adopted to treat the gas and liquid two-phase flow in channel. Meanwhile, the multiphase flow in porous electrodes is solved with the help of gas and liquid pressure conservation equations to reflect the liquid saturation jump phenomenon at two different porous electrodes (e.g. DL (diffusion layer) and CL (catalyst layer)). The effects of current density, methanol concentration and temperature on gas and liquid two-phase flow in channel and porous electrodes are investigated in detail. It is found that the carbon dioxide in anode channel gradually increases along flow direction and is mainly accumulated at the interface of anode channel and DL. Meanwhile, the carbon dioxide produced in ACL (anode catalyst layer) is likely to accumulate under the inlet region and then increases along flow direction gradually. Moreover, the higher the temperature, the more methanol crossover and the less carbon dioxide produced in DMFC because of the dissolution.